Work engagement pada karyawan: Bagaimana peran persepsi terhadap gaya kepemimpinan transaksional? - Sukma Megawati; Eben Ezer Nainggolan; Etik Darul Muslikah (INNER: Journal of Psychological Research, 2023)
Abstract The purpose of this study was to determine the relationship between the perception of transactional leadership style and work engagement among employees in Surabaya. This type of research that will be used is a quantitative approach with techniques of simple random sampling. The study sample consisted of 181 employees working in Surabaya. The scale used in this study is an adaptation of the scale that was created before, the Utrecht Work Engagement Scale (UWES) developed by Schaufeli and Bakker (2004) and scales Multifactor Leadership Questionnaire (MLQ) arranged by Bass (1985). The analysis technique used is the Parametric Test. Based on the results of data analysis using the Simple Linear Regression Test a correlation value or relationship is obtained, so which means that there is a positive relationship between perceptions of transactional leadership style with work involvement in employees in the city of Surabaya. The higher the level of perception of the transactional leadership style, the higher the level of work engagement that employees have, conversely the lower the level of perception of the transactional leadership style, the lower is work engagement that employees have. Keywords: Work engagement; Perception of Transactional Leadership Style; Employee.